2017
DOI: 10.23913/ricea.v6i12.91
|View full text |Cite
|
Sign up to set email alerts
|

Actitud hacia el etiquetado en productos genéticamente modificados en la población urbana de México / Attitude towards the Labeling of Genetically Modified Products in the Urban Population of Mexico

Abstract: Nuestro objetivo fue estudiar las actitudes de la población urbana mexicana con respecto al etiquetado de los productos transgénicos mediante el análisis transversal de una muestra probabilística de 14 mil 720 personas entre 18 y 65 años de edad. Sus actitudes hacia el etiquetado de productos (GM) fueron estudiadas y analizadas con un instrumento de 4 ítems binarios. Entre los resultados se encontró que 63.25 % de la muestra tiene el hábito de leer las etiquetas de los productos que consume; 93.69 % consideró … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In 4th sem nts (10.20%), ster to 526 stu Montesinos-López, et al, (2016) (93.59%), they propose that the label shows the characteristics of the product with GMO content. While, in the sample of university students (92.20%) in relation to the urban sample (93.69%) they propose that when promoting in any medium, a product with GMO content, the characteristics of the products should be made known to the individuals and finally, in the university students sample (92.50%), while in the urban sample (92.23%) agree that the Mexican government must legislate the corresponding legal framework to force the labeling of products with GMO content (Montesinos-López, et al, 2017). The above findings are consistent with studies conducted with students in Russia (Delmond et al, 2018), Kuwait (Nedaa & Al, 2018) and in India ( Kajale & Becker, 2013).…”
Section: Instrument and Sample Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 4th sem nts (10.20%), ster to 526 stu Montesinos-López, et al, (2016) (93.59%), they propose that the label shows the characteristics of the product with GMO content. While, in the sample of university students (92.20%) in relation to the urban sample (93.69%) they propose that when promoting in any medium, a product with GMO content, the characteristics of the products should be made known to the individuals and finally, in the university students sample (92.50%), while in the urban sample (92.23%) agree that the Mexican government must legislate the corresponding legal framework to force the labeling of products with GMO content (Montesinos-López, et al, 2017). The above findings are consistent with studies conducted with students in Russia (Delmond et al, 2018), Kuwait (Nedaa & Al, 2018) and in India ( Kajale & Becker, 2013).…”
Section: Instrument and Sample Of Participantsmentioning
confidence: 99%
“…It is relevant to point out that in 2015 a research was carried out in Mexico, at a national level, to know the perceptions and attitudes towards GMOs financed by the National Council of Science and Technology (CONACYT), with a sample of 14720 participants from the Mexican urban population, with people in a range of age between 18 to 65 years, in this study all 64 items of the questionnaire were dichotomous (Montesinos-López, et al, 2016). From the results of this survey these authors published a paper about the attitudes toward labeling of genetically modified products (Montesinos-López, et al, 2017), were they reported that 63.25% of the participants has the habit of reading the labels of the products that they consume. Also, they reported that 93.69% participants said that when companies advertise these types of products, they must show on the label the characteristics of the content, 93.59% want that products made with GMO show the characteristics of the content on the label and finally 93.23% agree that the Mexican government must legislate the corresponding legal framework, to force companies to label products with GMO content (Montesinos-López, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation